45 EFFECT OF OBESITY ON ATTENUATION-CORRECTED SINGLE-PHOTON EMISSION COMPUTED TOMOGRAPHY IMAGING. (1st January 2006) - Mehta, N.; Allison, S.; Heo, J.; Iskandrian, A. E.
Abstract : Background: Previous studies show that attenuation, scatter, and depth resolution correction (AC) improve the uniformity and diagnostic accuracy of single-photon emission computed tomography (SPECT) perfusion images. The effect of body mass index (BMI) on recovery of counts after AC and on nonuniformity is not well known and was investigated in this study. Methods: We identified 120 patients (60 men and 60 women) who had normal stress/rest gated SPECT perfusion imaging with Tc-99m tracer. Patients with prior myocardial infarction, coronary revascularization, left bundle branch block, and non-sinus rhythm were excluded. The patients were divided into 3 groups based on BMI. Group I had BMI < 25, group II 25 to 30, and group III > 30. The activity was counted in 9 segments per patient before and after AC. The percent increase was measured using the formula (corrected 2 uncorrected)/uncorrected 3 100. The uniformity was measured as percent difference between the highest and lowest segment counts both before and after AC. Results: There was a 6- to 10-fold increase in counts after AC ( p < .0001 in each group). The increase was 6.9 6 1.0 fold in group I, 8.6 6 1.4 fold in group II, and 10.5 6 1.8 fold in group III (p < .0001). The absolute counts after AC were less as BMI increased: 7, 820 6 2, 690 in group I, 6, 660 6 2, 690 in group II, and 6, 260 6 2, 310 in group III (p < .01 between group I vs II or III). The uniformity was not related to BMI as the maximum difference decreased from 29% before to 17% after AC in group I, 28% to 18% in group II, and 27% to 20% in group III (p = ns). Conclusion: AC results in marked count recovery that is dependent on BMI but an improvement in uniformity that is independent of BMI.